Etika Al-Qur’an dalam Dakwah di Era Disrupsi - Fatrin, Juan Muliawan; Hakim, Lukman Nul (Pubmedia Social Sciences and Humanities, 2024)
This research aims to explore and analyze the role of Quranic ethics in the context of preaching in the era of disruption. Disruption, often caused by technological changes and social transformations, has significantly impacted the way preaching is conducted. The focus of this research is to analyze how the ethical values embedded in the Quran can provide guidance for preaching practitioners in facing the new dynamics emerging in the era of disruption. The research methodology applied is qualitative, involving the study of Quranic literature related to the ethics of preaching. Additionally, the research includes an analysis of the implementation of these ethical values in the practice of preaching during the disruptive era. The findings of the research are expected to provide a profound understanding of the relevance of Quranic ethics in addressing the challenges and opportunities of preaching in the disruption era. Furthermore, it aims to lay the groundwork for the development of more contemporary ethical guidelines for preachers and preaching practitioners.